Sistem SCADA Implementasi Sistem SCADA Untuk Proses Koagulasi Pada Instalasi Pengolahan Air Berbasis PLC Schneider M221 dan HMI Weintek - Wanto, Ruwanto (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2023)
The importance of the need for clean water for human survival so that a water treatment system is needed. Conventional clean water treatment systems require a lot of labor and direct supervision from the operator. One of the automatic water treatment system innovations is using the SCADA system. This journal simulates a SCADA system for the coagulation process in water treatment installations. The main base of the SCADA system is the Schneider M221 PLC and the Weintek MT8071iP HMI